Increased 18F-Fluoroestradiol Uptake of Radiation Pneumonitis in a Patient With Metastatic Breast Cancer. (17th May 2023) - Pan, Bo; Hao, Zhixin; Zhou, Yidong; Sun, Qiang; Huo, Li
Abstract: A 42-year-old woman diagnosed with de-novo stage IV breast cancer underwent 18 F-fluoroestradiol (FES) PET/CT to evaluate the estrogen receptor status of metastatic lesions. The largest pulmonary nodule showed obvious FES uptake, consistent with pulmonary metastases from breast cancer. Interestingly, the images revealed a striking accumulation of FES in ground-glass attenuation in the left lobe of lung, suggestive of radiation pneumonitis.